Pengaruh Penggunaan Media E-comic Berbasis Etnomatematika Terhadap Hasil Belajar Siswa Kelas V SDN 3 Kota Bengkulu - Rahmadani, Alia; Agusdianita, Neza; Anggraini, Dwi (JURIDIKDAS, 2026)
This study aims to determine the effect of the use of ethnomathematics-based e-comic media on the learning outcomes of fifth grade students of SDN 3 Bengkulu City. The type of research used is quantitative using an experimental method with the Matching Only Pretest-Posttest Control Group Design design. The population in the study was fifth grade students of SDN 3 Bengkulu City, using a sampling technique, namely Cluster Random Sampling. The sample used in this study was class VA as the experimental group and class VB as the control group. The instrument used was a learning outcome test with aspects of knowledge in the form of multiple choice questions in the form of pretest-posttest. The type of research analysis technique is quantitative descriptive analysis, prerequisite test analysis, and hypothesis testing. With an average posttest value in mathematics learning in the experimental class of 75.36 and the control class 56.57. Hypothesis testing using the t-test, based on the results of the study obtained Sig. (2-tailed) = 0.001 <0.005 with a significance level of 4%. So there is a significant average difference between the learning outcomes of the experimental group and the control group and the experimental group using ethnomathematics-based e-comic media can affect student learning outcomes. So it can be concluded that there is an influence of the use of ethnomathematics-based e-comic media on the learning outcomes of fifth grade students of SDN 3 Bengkulu City.